Trajectories in waist circumference and waist-to-height ratio with left ventricular hypertrophy in childhood - Xuli Jin; Min Zhao; Jiahong Sun; Bo Xi (Frontiers in Nutrition, 2024)
Background and objectivePrevious studies have shown positive associations of waist circumference (WC) and waist-to-height ratio (WHtR) with left ventricular hypertrophy (LVH) among children and adolescents. However, most of these studies were cross-sectional or limited to only two time points. We aim to estimate the association of trajectories in WC and WHtR with LVH during childhood.MethodsData were from the prospective “Huantai Childhood Cardiovascular Health Cohort Study” conducted from 2017 to 2023 in Huantai County, Zibo City, Shandong Province. Group-based trajectory modeling was used to categorize WC into three groups: low-increasing, moderate-increasing, and high-increasing trajectories. Similarly, WHtR was categorized into three groups: stabilizing, decreasing, and increasing trajectories. Linear and log-binomial regression analyses were used to examine the associations of WC and WHtR trajectories with increased left ventricular mass index (LVMI) and LVH.ResultsA total of 946 children were included, with 51.9% being boys and an average age of 8 years at baseline. After adjustment for potential covariates, children in the high-increasing WC group and the increasing WHtR trajectory group had increased LVMI (β = 5.16 g/m2.7, 95% confidence interval (CI): 4.37, 5.95 and β = 4.91 g/m2.7, 95% CI: 4.15, 5.68) and a higher risk of LVH [risk ratio (RR) = 5.84, 95% CI: 3.39, 10.05 and RR = 7.38, 95% CI: 4.14, 13.14] compared to the low-increasing WC group and stabilizing WHtR group, respectively. Interestingly, the moderate-increasing WC and decreasing WHtR trajectory groups still have an increased LVMI (β = 2.83 g/m2.7, 95% CI: 2.05, 3.61 and β = 2.25 g/m2.7, 95% CI: 1.50, 3.01) and a higher risk of LVH (RR = 2.04, 95% CI: 1.00, 4.15 and RR = 2.23, 95% CI: 1.06, 4.71) compared to the low-increasing WC group and stabilizing WHtR group, respectively. Similar results were found when stratified by sex.ConclusionWe found the risk of LVH was not fully eliminated among children with a decreasing WHtR trajectory. These findings underscore the need for early prevention and continuous monitoring of WC and WHtR to help prevent future sub-clinical cardiovascular damage in childhood.